(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of mosaic embryo transfer at the National Center for Assisted Reproductive, National Hospital of Obstetrics and Gynecology in 2024. Subjects and methods: A retrospective study was conducted on 33 patients who underwent mosaic embryo transfer at the National Center for Assisted Reproductive, from January to December 2024. Results: The study population consisted of a clinically complex group, with 48.48% of patients ≥ 35 years. Ovarian stimulation demonstrated favorable outcomes, yielding an average of 7.76 ± 5.78 blastocysts. The ongoing pregnancy rate reached 30.3%, which was higher than that reported in several international studies, indicating the effectiveness of the embryo selection strategy. All live-born infants were delivered at term with normal birth weights (≥ 2500gr), confirming neonatal safety. These findings provide important real-world evidence to support the development and optimization of mosaic embryo transfer protocols in Vietnam. Conclusions: Mosaic embryo transfer represents a feasible and safe treatment option in cases where no euploid embryos are available. The degree and characteristics of mosaicism are key prognostic factors that should be carefully considered when developing embryo selection strategies.